in vitro Screening of Sesamum indicum Seeds for Antioxidant, Phytochemical and Biological Properties - Khan, Sheraz; Hashim Khan, Saniya; Ullah Khan, Inam; Inam, Wali; Asim, Muhammad; Hashim, Narmeen (Asian Journal of Chemistry, 2020)
Herbal medicines has been the most cost-effective and valuable medical practice to cure diseases and emphasize modern health care treatment. The present research was conducted to assess the biological activities of 10 fractions obtained from methanolic extract which was derived from dried seeds of Sesamum indicum. Antioxidant activity was assessed using DPPH radical scavenging, total antioxidant capacity and total reducing power assays. Highest free radical scavenging activity (80.3 ± 1.36%), total antioxidant capacity (104.7 ± 4.04 μg AAE/mg) and ferric reducing power activity (238.76 ± 1.23 μg AAE/mg) was shown by fraction SE. Fraction SE showed the highest phenolic contents (63.72 ± 1.5 μg GAE/mg) while fraction SG sample showed highest flavonoid contents (54.62 ± 2.61 μg QE QE/mg). Antibacterial activity was performed against four selected bacterial strains including Staphylococcus aureus, Escherichia coli, Enterobacter aerogens and Bacillus subtilis. Highest inhibition was shown by fraction SD (11 ± 1.04 mm) against Staphylococcus aureus, fraction SH against Bacillus subtilis (11 ± 1.06 mm) and fraction SB against Escherichia coli. All fractions were found inactive against the selected fungal strains. While performing antileishmanial activity, fraction SC showed highest percent mortality (78%) of Leishmania tropica. In brine shrimp lethality bioassay, fraction SG showed significant LD50 value (23.48 μg/mL).